Research in etiology of Floppy Kid Syndrome - Cheng, Cheng; Zheng, Yan; Wang, Xin; Tao, Jianping; Cheng, Darong (Frontiers in Veterinary Science, 2025)
Floppy Kid Syndrome (FKS) is a common and serious disease in goats, with incidence rates ranging from 10 to 50% and mortality rates between 20 and 60%. This study aimed to investigate the etiology of FKS through blood biochemical analysis and metagenomic sequencing. Blood biochemical analysis revealed metabolic disorders in FKS-affected goats, including acidosis and hypoglycemia. Metagenomic analysis showed marked gastric and gut dysbacteriosis, characterized by an increase in pathogenic bacteria such as Escherichia coli and Staphylococcus aureus, alongside a significant reduction in probiotic like Lactobacillus amylovorus. Furthermore, species diversity and richness were notably lower in FKS-affected goats compared to healthy goats. Based on these findings, we infer that FKS is a multifactorial disease caused by gastric and gut dysbacteriosis. The immaturity of the digestive system in newborn goats, combined with environmental stressors (such as sudden changes in weather), leads to gastric and gut dysbacteriosis, with a significant reduction in probiotic and an overgrowth of pathogenic bacteria. The dysbacteriosis, along with the inability to properly digest excessive milk intake, contributes to the accumulation of undigested milk in the digestive tract, creating an environment conducive to pathogenic bacteria growth. The fermentation of milk and the production of excessive lactic acid by pathogenic bacteria are absorbed into the bloodstream, causing acidosis and hypoglycemia. These metabolic disorders, in conjunction with the dysbacteriosis and systemic dysfunction, lead to the onset of FKS. These results underscore the critical role of gastric and gut dysbacteriosis in the pathogenesis of FKS, highlighting the need for targeted preventive and therapeutic strategies.